2015
DOI: 10.1016/j.infbeh.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Infant twins’ social interactions with caregivers and same-age siblings

Abstract: The study of twin behavior offers the opportunity to study differential patterns of social and communicative interactions in a context where the adult partner and same-age peer are equally familiar. We investigated the development of social engagement, communicative gestures, and imitation in 7- to 25-month-old twins. Twin dyads (N = 20 pairs) participated in ten-minute, semi-structured play sessions, with the mother seated in a chair completing paperwork for half the session, and on the floor with her childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Six-month-old infants tend to react to their peers, but need maternal support to continue the interaction, showing how mothers contribute to children's social engagement 11 . Adult support also helps the child to coordinate joint care with other children and is related to the increase in communicative offers in these meetings 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six-month-old infants tend to react to their peers, but need maternal support to continue the interaction, showing how mothers contribute to children's social engagement 11 . Adult support also helps the child to coordinate joint care with other children and is related to the increase in communicative offers in these meetings 4 .…”
Section: Discussionmentioning
confidence: 99%
“…As Amorim et al 1 point out, empirical studies have shown that infants interact with infants from an early age. Despite motor incompleteness, infants' broad repertoire of emotional, visual, auditory, olfactory, gestural and postural skills allow them to be active participants in interactions with their contemporaries 2 , demonstrating differential patterns of communicative and expressive resources 3 , and specificities in the development of social engagement 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we were interested in how twins would present with regard to risk factors for DLD (developmental language disorder) using a clinical tool combined with case history details' (p. 333). Foran et al (2021) indicated that the only other study of twins' gestures (Aldrich et al, 2015) found that twin toddlers were more likely to use showing gestures and other communicative/ interactive behaviors with their mothers than with their twin siblings. Here again, it is unfortunate that the zygosity of the participating pairs was not established by standard means; the eight same-sex pairs could have been MZ or DZ.…”
Section: Twins' Language and Gesture Delaysmentioning
confidence: 99%
“…The second group, which was concerned with the social aspect of the communication, presented two articles. The first one was a hybrid between expressive language abilities and prosocial behavior [3], and the last one was concerned with the social interactions of twin infants with their caregivers and same-age siblings [104].…”
Section: ) Skillsmentioning
confidence: 99%